Metabolome and transcriptome integration reveals insights into the process of delayed petal abscission in rose by STS - Zhang, Jingjing; Zhang, Yuyun; He, Yongmei; Du, Tingting; Shan, Duoxiu; Fan, Houdong; Wang, Wenyu; Qin, Zhe; Xin, Cuihua; Pei, Haixia (Frontiers in Plant Science, 2022)
The abscission of plant organs plays an important role in ensuring the normal life activities. Rose is one of the most important ornamental plants, and its premature abscission of petal has seriously affected the quality and commercial value. Silver Thiosulfate (STS) is an ethylene inhibitor, which is often used preservative to delay the senescence of fresh cut flowers. To understand the regulatory mechanism of petal abscission in rose by STS, integrative analysis of the metabolome and transcriptome profiles was performed in abscission zone (AZ) tissues of rose under different treatments (MOCK, STS, ETH, STS+ETH). The results showed that STS significantly delayed the petal abscission in phenotype and reduced the activity of two enzymes (pectinase and cellulase) associated with cell wall degradation in physiological level. STS affected the contents of five metabolites (shikonin, jasmonic acid, gluconolactone, stachyose and D-Erythrose 4-phosphate), and involved changes in the expression of 39 differentially expressed genes (DEGs) associated with these five metabolites. Five DEGs (LOC112192149, LOC112196726, LOC112189737, LOC112188495, and LOC112188936) were probably directly associated with the biosynthesis of shikonin, jasmonic acid, and D-Erythrose 4-phosphate. Meanwhile, the effect of STS on the abscission process significantly involved in the pentose phosphate pathway and amino acid biosynthesis pathway. In addition, STS had a greater effect on the transcription factors, phytohormone related DEGs represented by auxin and ethylene, DEGs related to disease resistance and amino acid, etc. Above all, STS negatively influences petal abscission of rose, these results maybe provide a reference for subsequent studies on petal abscission of rose by STS.